Lymph node stromal cells: subsets and functions in health and disease. Issue 10 (October 2021) - Grasso, C.; Pierie, C.; Mebius, R.E.; van Baarsen, L.G.M.
Abstract : Lymph nodes (LNs) aid the interaction between lymphocytes and antigen-presenting cells, resulting in adequate and prolonged adaptive immune responses. LN stromal cells (LNSCs) are crucially involved in steering adaptive immune responses at different levels. Most knowledge on LNSCs has been obtained from mouse studies, and few studies indicate similarities with their human counterparts. Recent advances in single-cell technologies have revealed significant LNSC heterogeneity among different subsets with potential selective functions in immunity. This review provides an overview of current knowledge of LNSCs based on human and murine studies describing the role of these cells in health and disease. Highlights: Single-cell RNA sequencing has uncovered conspicuous heterogeneity in lymph node stromal cells (LNSCs) populations in mice and humans. Human and mouse LNSC subsets show similarities in their transcriptomic profiles and trajectory analyses. Each LNSC subset has its own specific function in regulating immune responses. Human LNSCs have the machinery to regulate peripheral tolerance, making them attractive targets for modulating tolerance induction and maintenance. LNSCs in mice and humans can suppress T cell proliferation during strong inflammatory stimuli. Different mechanisms are utilized to perform this function. LNSCs from patients with particular autoimmune diseases exhibit altered functions and transcriptomic profiles. Stromal cells can enhance HIV-1 spread via trans -infection, thereby facilitating the infection of T cells. LNSCs might influence tumor progression and promote metastasis in several types of malignancies.